Anaerobic threshold – definition and how test - Vuksanovikj, Vladimir; Jovanovski, Jovan; Klincharov, Ilija; Aceski, Aleksandar; Tasevski, Zikica (My University, 2017)
Heart rate monitoring have been interesting method for monitoring the training Intensity. In to the training, some new technology has been introduced as a tool, which include GPS signal reading of movement of the athletes especially in group games. That equipment can present intensity and involvement of the athlete’s body from the training or match. But, even those tools are using heart rate monitor as important supported toll as they can give more accurate checking of the training intensity and body involvement of the athletes. This text provides basic information of heart rate monitoring, as well as testing and analysis of the anaerobic threshold. Anaerobic threshold (AT) represent the value of heart rate, in which the athletes body switch from aerobic in to anaerobic consuming of energy. As a separate value on the training, AT can show how much the athletes passed in to anaerobic energy consumption process, or above AT. But if one knows the speed achieved on AT (AT speed), then easily can be used to compare endurance capacity of two or more athletes. In this text 3 examples for testing the AT are provided, as well.
Keywords: anaerobic threshold; test; lactate curve; Shuttle run; heart rate monitoring; endurance; aerobic; anaerobic